2019
DOI: 10.1111/jne.12814
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal compromise contributes to programming of GABAergic and glutamatergic systems leading to long‐term effects on offspring behaviour

Abstract: Extensive evidence now shows that adversity during the perinatal period is a significant risk factor for the development of neurodevelopmental disorders long after the causative event. Despite stemming from a variety of causes, perinatal compromise appears to have similar effects on the developing brain, thereby resulting in behavioural disorders of a similar nature. These behavioural disorders occur in a sex‐dependent manner, with males affected more by externalising behaviours such as attention deficit hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 140 publications
0
20
0
Order By: Relevance
“…R. Soc. B 288: 20202467 to placental neurosteroids in utero is linked to a greater risk of developing attention deficit hyperactivity disorder, anxiety and other long-term behavioural consequences of pre-term birth [57,60,61]. Together, these findings strongly support the idea that maternally derived neurosteroids influence electrical activity in neurons and are essential for the normal development of neural function and behaviour.…”
Section: Maternal Steroids As Precursors For Neurosteroidsmentioning
confidence: 65%
See 1 more Smart Citation
“…R. Soc. B 288: 20202467 to placental neurosteroids in utero is linked to a greater risk of developing attention deficit hyperactivity disorder, anxiety and other long-term behavioural consequences of pre-term birth [57,60,61]. Together, these findings strongly support the idea that maternally derived neurosteroids influence electrical activity in neurons and are essential for the normal development of neural function and behaviour.…”
Section: Maternal Steroids As Precursors For Neurosteroidsmentioning
confidence: 65%
“…Action of GABA on these receptors decreases the likelihood of post-synaptic electrical activity in neural circuits. Neurosteroids, including those created from maternal steroid precursors, can increase or decrease the receptor's affinity for GABA, thereby altering the likelihood of action potentials [53,54], neural activity, and may have major implications for the developing nervous system [55][56][57][58][59][60][61][62]. Already, in very early stages of embryonic development, electrical activity is produced by neurons and GABA A receptors are expressed in neurons across tissues [63][64][65][66][67][68].…”
Section: Maternal Steroids As Precursors For Neurosteroidsmentioning
confidence: 99%
“…Moreover, an imbalance between inhibitory and excitatory action can occur if the enzyme responsible for the conversion of glutamate to GABA is affected. In addition, pregnancy challenges are associated with imbalanced excitatory-inhibitory pathways resulting from reduced GABAergic signaling or alterations in the maturation of inhibitory pathways in the brain, which could lead to behavior disorders (Shaw et al 2020). Our results show a significant impact of MgSO 4 on GAD67 (i.e.…”
Section: The Effect Of Mgso 4 On Dopamine and Gaba Expressionmentioning
confidence: 74%
“…Studies have shown that GAD67 performs over 90% of basal GABA synthesis in the human and rodent brain (Shaw et al 2020). Once synthesized from glutamate, GABA is then able to act on GABA A receptors to exert trophic and inhibitory action.…”
Section: The Effect Of Mgso 4 On Dopamine and Gaba Expressionmentioning
confidence: 99%
“…These events could be related to the homeostatic and protective actions of steroids in neural cells, as well as to the manifestation of sex differences in neurodegenerative disorders . The involvement of progesterone in neuroprotection and immunomodulation in Parkinson's disease is described in a mouse model in the study by Jarras et al Other neuroactive steroids are involved in complications of sleep deprivation, in the imbalance of inhibitory and excitatory actions during pregnancy that program for poor behavioural outcomes in a sex‐dependent manner later in life, in some psychiatric diseases such as Tourette's syndrome, and in the regulation of mitochondrial function in tauopathies …”
mentioning
confidence: 99%